Protecting Emergency Responders Volume 2 Community Views of Safety and Health Risks and Personal Protection Needs - LaTourrette, Tom (RAND Corporation, 2003)
Firefighters, law enforcement officers, and emergency medical service responders play a critical role in protecting people and property in the event of fires, medical emergencies, terrorist acts, and numerous other emergencies. The authors examine the hazards that responders face and the personal protective technology needed to contend with those hazards. The findings are based on in-depth discussions with 190 members of the emergency responder community and are intended to help define the protective technology needs of responders and develop a comprehensive personal protective technology research agenda.